Carotid Web Phenotype Is Uncommonly Associated With Classic Fibromuscular Dysplasia: A Retrospective Observational Study. Issue 2 (30th December 2021) - Sharashidze, Vera; Nogueira, Raul G.; Al-Bayati, Alhamza R.; Bhatt, Nirav; Nahab, Fadi B; Yun, Johanna; Allen, Jason W.; Frankel, Michael; Haussen, Diogo C
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Carotid web (CaW) is an intimal form of fibromuscular dysplasia (FMD) involving the carotid bulb which has been increasingly recognized as a potential cause of recurrent ischemic strokes. It is overlooked as a separate entity and often dismissed if no coexistent signs of classic FMD changes are observed. We aim to evaluate the frequency of classic FMD in high-yield vascular territories in patients with symptomatic CaW. Methods: This was a retrospective analysis of a symptomatic CaW database of 2 comprehensive stroke centers (spanning September 2014–October 2020). The diagnosis of a CaW during a stroke workup was defined as the presence of a shelf-like linear filling defect in the posterior aspect of the carotid bulb on computed tomography angiography in patients with acute ischemic stroke or transient ischemic attack of undetermined cause after a thorough evaluation. Neck computed tomography angiography and renal conventional angiography images were independently evaluated by two readers blinded to the laterality and clinical details to inspect the presence of underlying classic FMD. Results: Sixty-six patients with CaW were identified. Median age was 51 years (interquartile range, 42–57), and 74% were women. All patients had neck computed tomography angiography (allowing for bilateral vertebral and carotid evaluation), whereas 47 patients had additional digital subtraction angiography (which evaluated 47 carotids ipsilateral to the stroke and 10 contralateral carotids). Internal carotid artery classic FMD changes were noted in only 6 out of 66 (9%) in the ipsilateral carotids. No contralateral carotid or vertebral artery classic FMD changes were observed. Renal artery catheter-based angiography was obtained in 16 patients/32 arteries and only 1 patient/2 renal arteries demonstrated classic FMD changes. Conclusions: CaW phenotype is uncommonly associated with classic FMD changes. Coexistent classic FMD does not constitute a useful marker to corroborate or exclude CaW diagnosis.